Roots of Russia's war in Ukraine - Wood, Elizabeth A., 1958-; Pomeranz, William E.; Merry, E. Wayne; Trudoli͡ubov, Maksim (Washington, D.C : Woodrow Wilson Center Press ; New York : Columbia University Press, 2016)
"In February 2014, Russia initiated a war in Ukraine, its reasons for aggression unclear. Each of this volume's authors offers a distinct interpretation of Russia's motivations, untangling the social, historical, and political factors that created this war and continually reignite its tensions. What prompted President Vladimir Putin to send troops into Crimea? Why did the conflict spread to eastern Ukraine with Russian support? What does the war say about Russia's political, economic, and social priorities, and how does the crisis expose differences between the EU and Russia regarding international jurisdiction? Did Putin's obsession with his macho image start this war, and is it preventing its resolution? The exploration of these and other questions gives historians, political watchers, and theorists a solid grasp of the events that have destabilized the region."--Publisher's description
Introduction / Elizabeth A. Wood -- The origins of Russia's war in Ukraine: the clash of Russian and European "civilizational choices" for Ukraine / E. Wayne Merry -- Ground zero: how a trade dispute sparked the Russia-Ukraine crisis / William E. Pomeranz -- Russia's grand choice: to be feared as a superpower or prosperous as a nation? / Maxim Trudolyubov -- A small victorious war?: The symbolic politics of Vladimir Putin / Elizabeth A. Wood -- Conclusion / William E. Pomeranz.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Russo-Ukrainian War, 2014- -- Causes; Ukraine -- Foreign relations -- Russia (Federation); Russia (Federation) -- Foreign relations -- Ukraine; Guerre russo-ukrainienne, 2014- -- Causes; Ukraine -- Relations extérieures -- Russie; POLITICAL SCIENCE -- Security (National & International); Diplomatic relations; War -- Causes; Russia (Federation); Ukraine; Russisch-Ukrainischer Krieg; Internationale Politik; Ukraine; Russland; Internationella relationer; Krigsorsaker; Rysslands annektering av Krim 2014-; 2014